A Framework for the Heterogeneity and Ecosystem Services of Farmland Landscapes: An Integrative Review - Xiaohui Wang (MDPI AG, 2021)
It is essential for the sustainable development of farmland landscapes to balance ecosystem service trade-offs and improve resource use efficiency during crop production. Thus, an integrative and concept-centric qualitative approach was applied by combining the patch–corridor–matrix model of landscape ecology and the crop layout theory of farming systems into a theoretical framework. The thesis concludes that a farmland landscape comprises three compositions: the crop (the main crop and the service crop), the non-crop, and the non-vegetation, leading to heterogeneous composition and configuration. The main crop, typically displayed as large patches with a high distribution ratio, provides most of the provisioning services, while the service crop performs many regulation services. The non-crop and non-vegetation compositions often appear as strips that can connect different patches as corridors and support the provisioning services of crops. Non-crop compositions mainly focus on support and regulation services, while non-vegetation compositions support farming operations. Further research is needed in several respects, including the ecological impact and ecosystem service trade-offs of the composition and configuration heterogeneity, and strategies for the adoption of cropping systems and agronomic measures at the landscape scale, which are essential to the evaluation, improvement, and redesign of farmland landscapes.